Histórias de mães de crianças com a síndrome congênita do Zika vírus: caminhos entrelaçados de cuidado - Bulhões, Camilla de Sena Guerra (2019)
Objectives: Getting to know the histories of mothers of children with the zika vírus congenital syndrome and the path of care in the Healthcare Network. Method: Qualitative, descriptive and exploratory study, based on the methodological theoretical referential of the Oral History, more specifically, the Thematic Oral History. On the first phase of the study, the mixed method was used, regarding the application of the Self-Reporting Questionnaire, with 15 mothers from the collection, analysis and combination of techniques of research quantitative and qualitative in a same design of the research. In the second phase, individual interviews with 13 mothers were performed. Both the phases were performed in a Health Regional from the Estate of Pernambuco, Brazil. The data of the first phase of the study were typed and codified in an electronic spreadsheet of the software Excel version 2010. The interviews were transcribed and analysed with help of the sotware IRAMUTEQ, version 0.7. Results and discussion: It was observed that 10 women presented positive result for the mental suffering. The diagnostic of microcephaly of the children, resulting from the infection by the Zika virus, refer to the mothers since pregnancy demands of adaptation to the new style of life associated to the responsibility by the care. The living of the mothers with a disabled child is a phenomenon marked by therapeutic challenges, work overload, annulation, psychic suffering, the fear of loss/death or non-evolution of the picture of the child, the physical and psychological exhaustion due to the continuous care and the arising/worsening of conflicts that had a negative repercussion in the family dynamic, besides, individual confrontations using faith, and the social, which results of the relation of support with their social network. The comprehension of the stories of the mothers of children with the syndrome made possible the reflection on the challenges listed to the deficiency and the dependence of their children for daily care, the numerous problems on the path of the therapeutic itinerary, among them, the simultaneous use of the services, lack of reference in the city, structural problems on the Health Attention Network, gaps in the assistance to primary health, with consequent disarticulation and fragmentation in the care to the child and to the family. Final considerations: The context of the syndrome, associated to the low socioeconomic status, revealed the magnitude and peculiarity of the issue that permeates the limits to dignity, not only in the quality of life of the mothers, but in the precariousness of the life of women neglected by the Estate and society. Knowing the stories of these women makes possible to perceive their real necessities, supporting the health professionals in a critical decision making and in the elaboration of new strategies of care that value the self-care and strength of their identities and potentialities. That this investigation can enlarge horizons of research, elicit more intense discussions and new methodological perspectives for the studies that involve the therapeutic itinerary and the care of the mothers of children with deficiency, enabling visibilities for situations sometimes underestimated in the field of the practices and of the health and social policies.